初探中文奇幻电影中的生态意识 ：以《长江7号》、《捉妖记》和《捉妖记2》为例 = A study of ecocritical awareness in Chinese fantasy films using CJ7, monster hunt and monster hunt 2 as examples - 纪鸣凤 Kee, Ming Feng (Nanyang Technological University, 2020)
根据学者斯科特·麦克唐纳对于“生态电影”的看法，商业化电影因为无法实现“观点重塑”的功能，因此不能被纳入“生态电影”的讨论中。然而，商业电影真的对“生态讨论”毫无价值吗？ 本文将以三部奇幻喜剧电影，《长江7号》与《捉妖记》系列为研究对象。三部电影在主题上相似，提倡人类与异类和睦的关系，但是在这看似和谐的表面其实仍然基于压迫与被压迫的关系。因此，本文将以生态角度，通过“人与宠物关系”以及“变相种族歧视”（Covert Racism）等课题进行分析，探讨电影中人类与异类的关系，并且从中人与异类的死亡意识看出电影如何通过异类体现人类对于长生的欲望。此外，本文也将对电影中的电脑科技运用以及音乐进行分析，探讨这些电影手法如何帮助观众对生态有更好的诠释。 本文的末章将尝试对麦克唐纳“生态电影”定义做出回应，讨论商业电影的“生态”价值以及随着科技发展，如何运用科技平台将生态反思延续至戏院外，通过讨论起到“观点重塑”的效果，解决因对“生态电影”的既定的要求而产生被动的生态关怀反思。最后，“生态电影”的“观念重塑”目的不应针对一部电影，而是将几部电影的观看作为互文，达到对生态课题的“观念重塑”。 According to Scott Macdonald’s definition of “Ecocinema”, commercial movie should not be included in the discussion of as it does not offer an alternate view to conventional media-spectatorship in helping to nurture a more environmentally progressive mindset, but is it true that commercial films offer no value to the discussion of “Ecocinema” ? This paper aim to perform a close reading on three Chinese commercial fantasy films: CJ7 and Monster Hunt series. These films have a common theme of portraying a harmonious human and non-human relationship, but under this harmonious façade, lies an entity which succumbs to oppression in order to maintain the relationship. As such, this paper will analyse this relationship through an ecological perspective by discussing topics such as “human and pets” relationship as well as “Covert Racism” to examine the portrayal of human and non-human relationship in the films. The analysis of the relationship would also examine how humans’ desire for longevity is being portrayed via non-human species through their difference in perception of death. The last part of the essay attempts to address Scott Macdonald’s idea on “Ecocinema” and discuss the value that commercial films may contribute to the restructuring of ecological perceptions. The paper also suggests that the progress of “Ecocinema” should tap on the developments of technology to bring reflections beyond cinema. Discussions via online platforms may allow interactions of new perceptions to take place, encouraging audiences to review the film. This then addresses the potential issue of passive reflection that “Ecocinema” may bring if audiences rely solely on the expectations of viewer’s experience that “Ecocinema” emphasised. Lastly, the objective of restructuring perception of ecological aspects should not be focused on one film, rather, a collective approach should be taken, where it may take a few films to achieve the objective.